2013
DOI: 10.3389/fgene.2013.00002
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Interactions between NAFLD and Xenobiotic Metabolism

Abstract: Non-alcoholic fatty liver disease (NAFLD), the hepatic manifestation of the metabolic syndrome, is a complex multifactorial disease characterized by metabolic deregulations that include accumulation of lipids in the liver, lipotoxicity, and insulin resistance. The progression of NAFLD to non-alcoholic steatohepatitis and cirrhosis, and ultimately to carcinomas, is governed by interplay of pro-inflammatory pathways, oxidative stress, as well as fibrogenic and apoptotic cues. As the liver is the major organ of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 194 publications
(210 reference statements)
3
44
1
Order By: Relevance
“…PXR is a ligand‐activated nuclear receptor that, upon activation, forms a heterodimer with RXR. This complex is not only activated by exogenous toxins but has also been shown to responds to endobiotics like bile acids and steroid hormones 79, 80. Previous studies have shown that PXR activation in mice induces fatty acids uptake via upregulation of Cd36 , which is one of the 148 consistently regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…PXR is a ligand‐activated nuclear receptor that, upon activation, forms a heterodimer with RXR. This complex is not only activated by exogenous toxins but has also been shown to responds to endobiotics like bile acids and steroid hormones 79, 80. Previous studies have shown that PXR activation in mice induces fatty acids uptake via upregulation of Cd36 , which is one of the 148 consistently regulated genes.…”
Section: Discussionmentioning
confidence: 99%
“…Although genetic variation clearly plays a role in the occurrence of ADRs, other factors such as liver diseases are also known to alter drug pharmacokinetics and contribute to the occurrence of ADRs (Verbeeck, 2008;Merrell and Cherrington, 2011;Gandhi et al, 2012;Naik et al, 2013). Liver diseases that impair hepatic function may require dose adjustments to maintain drug concentrations within the therapeutic window and avoid ADRs (Delcò et al, 2005;Verbeeck, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Another location where ROS is generated is in microsomes. FFA is the inductive agent of P450-2E1, which occupies an important position in the cascade of ROS and lipid peroxidation generation (6). In microsomes, FFAs are easily oxidized and degraded into acyl-CoA.…”
Section: Pathogeneisismentioning
confidence: 99%
“…Excessive oxidative stress derives from mitochondrial dysfunction and iron overload. The unceasingly increased ROS, and the product of oxidative stress, results in the rapid depletion of ATP, DNA injury, instability of protein and release of inflammatory factors, sequentially break cellular completeness of structure and function, which promotes the development of NAFLD (6,10).…”
Section: Gene Polymorphisms In Mediators Of Oxidative Stressmentioning
confidence: 99%